Involvement of Met and Kr-h1 in JH-Mediated Reproduction of Female Bactrocera dorsalis (Hendel) - Yue, Yong; Yang, Rui-Lin; Wang, Wei-Ping; Zhou, Qi-Hao; Chen, Er-Hu; Yuan, Guo-Rui; Wang, Jin-Jun; Dou, Wei (Frontiers in Physiology, 2018)
Juvenile hormone (JH) prevents metamorphosis during insect larval stages and promotes adult reproductive processes. Krüppel-homolog 1 (Kr-h1), a zinc finger transcription factor assumed to be induced by JH via the JH receptor methoprene-tolerant (Met), mediates the antimetamorphic effect of JH in insects, but its function in JH-mediated reproductive processes has not been fully explored. In this study, Met and Kr-h1 involved in the JH signaling pathway were first cloned and identified from the oriental fruit fly, Bactrocera dorsalis, an important pest infesting fruit and vegetables worldwide. Subsequent spatiotemporal expression analysis revealed that Met and Kr-h1 were both highly expressed in 7-day-old adults and fat body of female adults, respectively. Treatment with a JH analog (methoprene) significantly induced the expression of JH signaling and vitellogenin genes and accelerated ovary development. RNA interference (RNAi) further revealed that either Met or Kr-h1 depletion at the adult stage of B. dorsalis impeded ovary development, with significantly lower egg production noted as well. In addition, rescue through methoprene application after RNAi stimulated the expression of JH signaling and vitellogenin genes. Although there were still differences in ovary phenotype between rescued insects and the pre-RNAi control, ovary redevelopment with a larger surface area was observed, consistent with the spatiotemporal expression and phenotypes recorded in the original methoprene experiment. Our data reveal the involvement of Kr-h1 in insect vitellogenesis and egg production, thus indicating the crucial role of the JH signaling pathway in insect reproduction.